Autopsy Patients With Obesity or Metabolic Syndrome as Basic Cause of Death: Are There Pathological Differences Between These Groups? - Concalves, Lucas Braz [UNESP]; Miot, Helio Amante [UNESP]; Custodio Domingues, Maria Aparecida [UNESP]; Oliveira, Cristiano Claudino [UNESP] (Sage Publications Ltd, 2018)
BACKGROUND: The objectives of this study were the evaluation of pathological characteristics of patients with obesity or metabolic syndrome (MS) as basic cause of death, associating the autopsy findings with some clinical aspects and the abdominal adipose panicle thickness. METHODS: A total of 88 autopsy cases were studied, divided into 2 groups based on the main cause of death: group 1 (n=15) obesity and group 2 (n=73) MS. Clinical summaries of autopsy requests. macroscopic findings. and histologic sections were reviewed. RESULTS: The definition of obesity as the basic cause of death is associated with larger thickness of the abdominal adipose panicle, being 8.5cm (P= .001) the best measurement, according to the receiver operating characteristic curve. Hypertensive cardiopathy (P=.001), ischemic cardiopathy (P=.003), coronary (P= .008)/systemic (P=.005) atherosclerosis, and arterial (P=.014)/arteriolar (P=.027) nephrosclerosis are associated with the diagnosis of MS. Steatohepatitis is associated with the diagnosis of obesity (P=.030); however, its association with the thickness of the abdominal adipose panicle is not statistically significant (P=.211). CONCLUSIONS: In the context of an obese patient in autopsy, pathologist may use the information about abdominal adipose panicle associated with heart. kidney. and liver findings. even macroscopic ones, to decide the basic cause death between obesity and MS.
Keywords: Autopsy; metabolic X syndrome; obesity